A new species of the genus Nyereria Mason (Hymenoptera: Braconidae: Microgastrinae) fromVietnam - Long, Khuat Dang; Achteberg, Cornelis van (Academia Journal of Biology, 2015)
Nyereria Mason, 1981 is a medium-sized genus of the subfamily Microgastrinae (Braconidae) with two species already known from Vietnam, viz. Nyereria albicentrus Long & van Achterberg, 2008 and N. yenthuyensis Long & van Achterberg, 2008. In this paper, a new species of this genus is described and illustrated: Nyereria bicolorata Long & van Achterberg, sp. n.. The checklist and distribution of the twenty three named species are given, of those eighteen species are described from the Afrotropical region and four species from the Oriental region. One species is known from the East Palaearctic region. A key to the species of the genus Nyereria from Vietnam is provided.